The price of a sex offense conviction - Huebner, Beth M. (Criminology, 2022)
Monetary sanctions can expand the scope and depth of punishment. Most research on monetary sanctions has centered on fines and fees assessed by the court, but they are also routinely imposed as part of the probation and parole sentence. In this article, we draw on in-depth interview data from a sample of individuals under correctional supervision to document the often hidden costs of correctional control. We further consider a subsample of participants convicted of sexual offenses to illustrate the unique way that monetary sanctions are levied on groups of people who are considered more morally culpable and worthy of carceral control. We find that monetary sanctions are regularly assessed and challenging for most participants. The stigma of a sexual offense conviction and economic precarity, particularly among Black members of the sample, further the costs of punishment. We contend that costs associated with a sexual offense are unique because they can continue in perpetuity, govern normative behavior, and are centered on an assumption of continued guilt. We argue that the monetary sanctions levied against convicted persons, especially individuals with sexual offenses, demonstrate the often hidden and expansive nature of carceral control for other marginalized groups